Uji Daya Hambat Ekstrak Etanol Tumbuhan Sarang Semut (Myrmecodia Pendans) Asal Maluku terhadap Bakteri Escherichia Coli - Djarami, Jayanti (JURNAL KESEHATAN MALUKU HUSADA, 2024)
ABSTRACIntroduction: The anthill plant (Myrmecodia pendans) is one of the plants that is often used by the community as a traditional medicine. The phar cological effect of the anthill plant (Myrmecodia pendans) is that it can treat diarrhocal diseases caused by Escherichia coli. Objective: To determine the antibacterial activity of anthill plants (Myrmecodia pendans) from Maluku against the growth of  Escherichia coli bacteria. Methods: Using a laboratory experimental study with an agar diffusion method research design. Results: Phytochemical screening of anthill plants (Myrmecodia pendans) showed that anthill plants (Myrmecodia pendans) positively contain secondary metabolite compounds such aflavonoids and tannins. Antibacterial activity ting of anthill plant extract (Myrmecodia pendans) against the growth of Escherichia coli bacteria obtained the average diameter of the inhibition zone at a concentration of 15% which is 9.26 mm, at a concentration of 30% which is 9.47 mm at a concentration of 60% which is 12.5 mm, and a concentration of 90% which is 18.20 mm for comparative control, namely cotrimoxazole antibiotics, the diameter of the inhibition zone is 20.27 mm. Conclusion: The anthill plant (Myrmecodia pendans) has activity as antibacterial Escherichia coli.Keywords: Ant nest plant (Myrmecodia pendans), Escherichia coli.